Heat-related mortality as an indicator of population vulnerability in a mid-sized central European city (Novi Sad, Serbia, summer 2015) - Arsenović, Daniela; Savić, Stevan; Lužanin, Zorana; Radić, Ivana; Milošević, Dragan; Arsić, Miodgrag (Geographica Pannonica, 2019)
Hot summers with several intensive heat waves lead to strong heat-related mortality in Central and Southeast European cities. Therefore, the aim of the study was to evaluate association between maximum temaprature and mortality during the summer period in 2015 and to contribute to the future long-term assessment of heat-related mortality in urban population. The daily number of deaths of all causes and cause-specific mortality for the population of Novi Sad were used, as well as hourly air temperature data from the Novi Sad urban network (NSUNET) system. Four heat waves were detected using the Huth and Kysely methods. Three heat wave periods lasted longer than ten days. In July and August, 45% of days had a maximum temperature above 30 ºC, and more than 70% of days had a maximum temperature above 25 ºC. The average number of deaths was higher during the heat wave days. Significant association was found between Tmax and all-cause, cardiorespiratory, non-cardiorespiratory in total population, all-cause and cardiorespiratory mortality in the age group 65 and over. This study demonstrates a high magnitude of relation between mortality and temperature. Finally, the results show that population in urban areas is highly vulnerable during heat waves.
Keywords: mortality; heat waves; high temperature; urban population; Serbia